Knowledge and Attitudes Regarding Cervical Cancer Risk Factors and Screening - Dr. Renu Verma; Dr. Mini, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: - Cervical cancer remains a leading cause of morbidity and mortality among women worldwide, particularly in low- and middle-income countries. Despite advances in screening and prevention, late detection contributes significantly to poor outcomes. Identifying gaps in knowledge and understanding prevailing attitudes toward screening can guide targeted interventions to improve early detection and reduce disease burden. Methods: - A cross-sectional survey was conducted among 450 women aged 30 years and above in selected healthcare facilities. Participants were recruited through stratified or convenience sampling methods, depending on resource availability. Data were collected using a validated, self-administered questionnaire covering sociodemographic factors, knowledge of risk factors (e.g., early sexual debut, smoking, weak immune system), and attitudes toward screening. Descriptive analyses were performed to summarize participant characteristics. Inferential statistics, including Chi-square tests and multivariate regression, were used to assess associations between knowledge, attitudes, and screening uptake. Ethical approval was obtained before data collection. Results: - Most respondents (89.8%) identified early sexual debut as a risk factor, while 94.2% acknowledged smoking as a contributing factor. However, only 2.4% recognized immunocompromised status as a risk factor. Over 98% of participants were aware of cervical cancer screening, yet barriers to screening persisted, including perceived lack of necessity (34.9%), uncertainty about locations offering Pap smears (16.7%), and underestimation of personal risk (45.3%). Conclusion: - The study highlights substantial awareness of certain cervical cancer risk factors but identifies persistent misconceptions and barriers related to screening. Interventions should focus on clarifying risk factors, bridging knowledge gaps regarding screening facilities, and addressing attitudinal barriers to encourage regular screening.